Resisting categories Latin American and/or Latino? - Ramírez, Mari Carmen, 1955-; Ybarra-Frausto, Tomás, 1938-; Olea, Héctor; Gaztambide, María C.; Kervandjian, Melina (Critical documents of 20th-century Latin American and Latino art, 2012)
"This anthology of more than 165 seminal writings by influential twentieth- and twenty-first century artists and critics who explore and challenge complex definitions of what it means to be 'Latin American' or 'Latino' is designed to be an indispensable tool for the study of Latin American and Latino art"--